Pemikiran Filsafat Pendidikan Islam Perspektif Seyyed Hossein Nasr Dan Relevansinya Di Era Pendidikan Modern - Sri Juwita; Adang Hambali; Andewi Suhartini (Fakultas Tarbiyah, Universitas Darussalam Gontor, 2023)
This article aims to find out philosophical thoughts according to Hussein Nasr in criticizing education, besides looking for the relevance of his thoughts in Islamic Education in the modern era. This research is qualitative in the form of an in-depth search related to certain discussions. Data collection uses literature studies by collecting data and taking discussions relevant to research from related sources. The method used is the content analysis which is carried out by analyzing the content of library sources. The results showed that Hossein Nasr's thought was influenced by Perennial philosophy, which prioritized traditional wisdom in Islam. Nasr's thought was a reaction to the crisis of modern civilization. In Islamic education, Nasr gave his reconstruction of the basics of Islamic educational philosophy, the nature and purpose of education, curriculum, methods, and educational environment. Nasr's thoughts on the philosophy of Islamic education are relevant to be applied today, considering that Islamic education is in a moral and spiritual crisis influenced by modern civilization. The concept of Nasr's perspective educational philosophy can be implemented in modern education. This research can be useful to add to the treasures of Islamic education and make new contributions to be applied to Islamic education in the modern era.